Aplikasi Model Adaptasi Roy pada Anak dengan Gangguan Keseimbangan Nutrisi - Amelia Hartika Rani; Dwi Budiyati; Nyimas Heny P (Universitas Malahayati Lampung, 2024)
ABSTRACT Typhoid fever is a tropical disease that often attacks children, especially toddlers, and can cause problems with the digestive system and affect the level of consciousness. Adequate nutrition plays an important role in increasing the body's endurance, accelerating healing, and preventing complications and recurrence. Roy's adaptation model can support patients in responding adaptively. To evaluate the effectiveness of the application of the Roy adaptation model in overcoming nutritional balance disorders in children with typhoid fever. Case study of two pediatric patients with typhoid fever who experienced nutritional balance disorders. Nursing interventions are carried out using the Roy adaptation model approach. Both patients successfully adapted to nutritional balance disorders. Second management patients show faster adaptation and recovery than first treatment patients. Factors that influence the success of adaptation include the client's age, parental support, environmental temperature, stress level, and severity of illness. Conclusion: Application of the Roy adaptation model is effective in supporting the adaptation of pediatric patients with typhoid fever to nutritional balance disorders. The nurse's ability to manage stimuli that affect the patient's nutritional status plays an important role in increasing the patient's adaptive capacity. Keywords: Roy Adaptation, Nutritional Disorders, Gastrointestinal System, Typhoid Fever ABSTRAK Demam tifoid merupakan penyakit tropis yang sering menyerang anak-anak, terutama balita, dan dapat menimbulkan gangguan pada sistem pencernaan serta mempengaruhi tingkat kesadaran. Nutrisi adekuat berperan penting dalam meningkatkan daya tahan tubuh, mempercepat penyembuhan, dan mencegah komplikasi serta kekambuhan. Model adaptasi Roy dapat mendukung pasien dalam merespon secara adaptif. Mengevaluasi efektivitas aplikasi model adaptasi Roy dalam mengatasi gangguan keseimbangan nutrisi pada anak dengan demam tifoid. Studi kasus pada dua pasien anak dengan demam tifoid yang mengalami gangguan keseimbangan nutrisi. Intervensi keperawatan dilakukan menggunakan pendekatan model adaptasi Roy. Kedua pasien berhasil beradaptasi terhadap gangguan keseimbangan nutrisi. Pasien kelolaan kedua menunjukkan adaptasi dan pemulihan yang lebih cepat dibandingkan pasien kelolaan pertama. Faktor-faktor yang mempengaruhi keberhasilan adaptasi meliputi usia klien, dukungan orang tua, temperatur lingkungan, tingkat stres, dan tingkat keparahan penyakit. Aplikasi model adaptasi Roy efektif dalam mendukung adaptasi pasien anak dengan demam tifoid terhadap gangguan keseimbangan nutrisi. Kemampuan perawat dalam mengelola stimulus yang mempengaruhi status nutrisi pasien berperan penting dalam meningkatkan kemampuan adaptasi pasien. Kata Kunci: Adaptasi Roy, Gangguan Nutrisi, Sistem Gastrointestinal, Demam Tifoid